One-Dimensional Modeling of the Pressure Loss in Concrete Pumping and Experimental Verification - Xuan Zhao; Guoqiang Gao; Minshun Wan; Juchuan Dai (Applied Sciences, 2024)
An accurate formula for calculating the pressure loss in concrete pumping plays a significant guiding role in the design and service process of pump trucks. Based on the flow characteristics of concrete pumping, a straight pipe one-dimensional model for the pressure loss is developed, in which both the viscous force of the mortar in the lubrication layer and the blocking effect of coarse aggregate particles are considered. First, the complex geometrical shapes of the aggregate particles are geometrically reconstructed by using a HandySCAN noncontact scanner and the reverse modeling software Geomagic Design X (v.19.0.2). Then, the equivalent spherical size of nonspherical aggregate particles is calculated according to the equal hydraulic radius principle. The blocking effect of the aggregate particles is converted into the wall roughness. Finally, an explicit expression for the pressure loss in concrete pumping is deduced by using Modi’s equation, Bernoulli’s equation, and Darcy’s formula, and the calculated value is compared with the measured value at a corresponding experimental site. The results indicate that the pressure loss values calculated with the one-dimensional flow model are closer to the actual pumping pressure loss values. The relative error between the results and the actual pumping pressure loss value is about 20.2%.